Dampak Ekowisata Mangrove Terhadap Pendapatan Keluarga Di Desa Budo Kecamatan Wori Kabupaten Minahasa Utara - Hutahaean, Ezra Gabriella; Kapantow, Gene; Baroleh, Jenny (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The purpose of this study was to determine the impact of developing mangrove eco-tourism on family income in Budo Village, Wori District, North Minahasa Regency. This research was carried out for 3 (three) months, from May to July 2023. The data collected are primary data collection was obtained through interviews guided by the questionnaire. Secondary data collection is carried out by collecting data through literature studies such as documents, writings or research results and various references that are relevant to the research problem in the form of books, litera-ture, internet and other sources related to this research. To compare the income between the two groups of families, the average difference test known as the t-test is used. The results of this study indicate that the existence of mangrove tourism in Budo Village makes a positive contribution to increasing people's income. The average income of people who earn from ecotourism is signifi-cantly higher than that of people who do not earn from ecotourism. From the results of calculating family income, the income of families who earn from ecotourism is Rp. 1,676,666 higher than the income of families who do not earn from ecotourism